Empathy and Modern Technology: A Neuroergonomics Perspective. Issue 2 (20th October 2015) - Wachowicz, Barbara; Lewandowska, Koryna; Popek, Anna; Karwowski, Waldemar; Marek, Tadeusz
Abstract: The primary purpose of this paper is to discuss the role of empathy in the design of advanced systems in manufacturing and service industries in order to ensure suitable working conditions for employees from the social and technological point of view. The origins and components of empathy are briefly reviewed. The neural underpinnings of three components of empathy, including cognitive, emotional, and behavioral aspects, are considered in the context of human–human and human–machine interactions, as well as design of working environments. Finally, the potential advantages of applying empathy‐related knowledge to the design and development of human‐centered technology are discussed.